Quasi Semi and Pseudo Semi (p,E)-Convexity in Non-Linear Optimization Programming - Hazim, Revan I.; Majeed, Saba N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The class of quasi semi -convex functions and pseudo semi -convex functions are presented in this paper by combining the class of -convex functions with the class of quasi semi -convex functions and pseudo semi -convex functions, respectively. Various non-trivial examples are introduced to illustrate the new functions and show their relationships with -convex functions recently introduced in the literature. Different general properties and characteristics of this class of functions are established. In addition, some optimality properties of generalized non-linear optimization problems are discussed. In this generalized optimization problems, we used, as the objective function, quasi semi -convex (respectively, strictly quasi semi -convex functions and pseudo semi -convex functions), and the constraint set is -convex set.